What causes low magnetization at basalt‐hosted hydrothermal sites? Insights from inactive site Krasnov (MAR 16°38′N). (29th April 2014) - Szitkar, Florent; Dyment, Jérôme; Choi, Yujin; Fouquet, Yves
Abstract High‐resolution magnetic surveys acquired near the seafloor show that active basalt‐hosted hydrothermal sites are associated with zones of lower magnetization. This observation may reflect the thermal demagnetization of a hot hydrothermal zone, the alteration of basalt affected by hydrothermal circulation, and/or the presence of thick, nonmagnetic hydrothermal deposits. In order to discriminate among these inferences, we acquired vector magnetic data 50 m above inactive hydrothermal site Krasnov using the Remotely Operated Vehicle (ROV) Victor. This deep hydrothermal site, located 7 km east of the Mid‐Atlantic Ridge (MAR) axis at 16°38′N, is dissected by major normal faults and shows no evidence of recent hydrothermal activity. It is therefore a perfect target for investigating the magnetic signature of an inactive basalt‐hosted hydrothermal site. Krasnov exhibits a strong negative magnetic anomaly, which implies that the lower magnetization observed at basalt‐hosted hydrothermal sites is not a transient effect associated with hydrothermal activity, but remains after activity ceases. Thermal demagnetization plays only a secondary role, if any, in the observed magnetic low. Forward models suggest that both the nonmagnetic hydrothermal deposits and an altered zone of demagnetized basalt are required to account for the observed magnetic low. The permanence of this magnetic signature makes it a useful tool to explore midocean ridges and detect inactive hydrothermal sites.